Indigenized Domino Activity Method: Its Effectiveness on Fraction Preliminaries Skills of Blaan Pupils - Sherlyn Mae P Alboroto (ASEAN Journal of Basic and Higher Education, 2021)
Indigenized Domino Activity method refers to the use of concrete object which is the contextualized domino as aid on visualization and games in improving Fraction Preliminaries Skills of the pupils. This study aimed to find out the effectiveness of Indigenized Domino Activity method on the fractions preliminaries skills of Grade V Blaan pupils. The study employed experimental research design specifically single subject research. It is quantitative by nature that was complemented by qualitative information. It involved forty-eight (48) subjects who were officially enrolled in Ondok Gawan Elementary School addresses during the school year 2016-2017. Test, interview, and pictorial representation were employed to gather the needed data. The statistical tools employed were frequency count, percentage rate, weighted mean, and t-test for dependent samples. The result of the study revealed that the subjects have low fraction preliminaries skills before the indigenized domino application and have high level of fraction preliminaries skills after the intervention. Therefore, indigenized domino activity method is an effective teaching intervention to improve the fraction preliminaries skills of the pupils. The study suggested that the school and teachers should indigenize the lesson activities to improve the fraction preliminaries skills of the pupils.